A survivable colorless wavelength division multiplexed passive optical network with centrally controlled intelligent protection scheme - Zhong, Wende (2014)
Several protection schemes have been proposed for wavelength division multiplexed passive optical networks (WDM-PONs). However, these existing schemes only work under the assumption that all the optical network units (ONUs) and the optical light terminal (OLT) continuously transmit optical signals. In practice, some ONUs may be in sleep mode to save power consumption or may be shut down whenever users are offline. Under such scenarios, the existing schemes would not work. To deal with more practical operation scenarios, we propose a centrally controlled intelligent protection scheme for survivable WDM-PONs, whereby the optical power on both the working and protection paths is monitored simultaneously, and the monitored results are fed to a novel logical decision unit which performs the protection switching. It provides 1:1 downstream protection and 1+1 upstream protection capabilities. The logic decision unit in conjunction with a power monitoring unit is implemented in the OLT to enable intelligent protection switching in more practical operation scenarios. Moreover, our proposed protection scheme can tell the connection status of every fiber path (working and protection), thus facilitating a faster failure recovery. The scheme feasibility is experimentally verified with 10 Gb/s downstream and 1.25 Gb/s upstream transmissions. The network performances in terms of complexity and availability are also evaluated.